2017
DOI: 10.1037/dev0000344
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial and human capital pathways to socioeconomic exclusion: A 42-year prospective study.

Abstract: Nordic welfare states have been very successful at reducing poverty and inequality among their citizens. However, the presence of a strong social safety net in these countries has not solved the problem of socioeconomic exclusion, manifesting in such outcomes as chronic unemployment and welfare dependency. In an effort to understand this phenomenon, the current study builds on the assumption that psychological risk factors emerge as important determinants of socioeconomic disadvantage in an environment where a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…People who are excluded from the labor market face large personal and economic costs (Brand, 2015). They are more likely to experience psychological distress, social marginalisation, financial hardship, higher welfare support needs, and earlier mortality (Paul, & Moser, 2009; Roelfs, Shor, Davidson, & Schwartz, 2011; Savolainen, Mason, Lyyra, Pulkkinen, & Kokko, 2017; Schmitz, 2011). Although the causal antecedents of economic exclusion and long-term welfare receipt are complex, involving both individual characteristics and structural systemic factors, it has been repeatedly observed that children with behavioral problems are more likely to experience economic difficulties in adulthood, including unemployment, lower earnings, and less wealth (Fergusson, Boden, & Horwood, 2013; Healey, Knapp, & Farrington, 2004; Knapp, King, Healey, & Thomas, 2011; Rivenbark et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People who are excluded from the labor market face large personal and economic costs (Brand, 2015). They are more likely to experience psychological distress, social marginalisation, financial hardship, higher welfare support needs, and earlier mortality (Paul, & Moser, 2009; Roelfs, Shor, Davidson, & Schwartz, 2011; Savolainen, Mason, Lyyra, Pulkkinen, & Kokko, 2017; Schmitz, 2011). Although the causal antecedents of economic exclusion and long-term welfare receipt are complex, involving both individual characteristics and structural systemic factors, it has been repeatedly observed that children with behavioral problems are more likely to experience economic difficulties in adulthood, including unemployment, lower earnings, and less wealth (Fergusson, Boden, & Horwood, 2013; Healey, Knapp, & Farrington, 2004; Knapp, King, Healey, & Thomas, 2011; Rivenbark et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The individual characteristics that contribute to youth unemployment and subsequent welfare receipt have been extensively debated both inside and outside academia and the role of both proximal and distal factors are generally acknowledged. Proximal factors describe immediate precipitating events, such as accidents or illness, that lead to employment loss and subsequent welfare needs, while distal factors concern temporally distant events or personal characteristics that may stretch far back into childhood (Savolainen et al, 2017). According to one influential view, youth unemployment is the consequence of failed accumulation of capital – human, social, and personal capital – across the early life course (Caspi, Wright, Moffitt, & Silva, 1998; Converse, Piccone, & Tocci, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…18 Adults who demonstrate antisocial behaviors may experience many difficulties in developing and maintaining positive relationships, have trouble sustaining successful employment, and have problems with the law, among other challenges. 19 , 20 , 21 Antisocial behaviors are generally found to be more prevalent among men compared with women, again making the examination of sex differences an important consideration. 22 , 23 , 24 Harsh physical punishment and child maltreatment are likely associated with antisocial behaviors among men and women in the general population in the United States—the extent, however, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Antisocial features of antisocial personality disorder as defined in the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) ( DSM-5 ) include failure to conform to the law, lack of ethical behavior, absence of concern for others while being deceitful, and irresponsible, manipulative, and risk-taking behaviors . Adults who demonstrate antisocial behaviors may experience many difficulties in developing and maintaining positive relationships, have trouble sustaining successful employment, and have problems with the law, among other challenges . Antisocial behaviors are generally found to be more prevalent among men compared with women, again making the examination of sex differences an important consideration .…”
Section: Introductionmentioning
confidence: 99%